IEEE SENSORS 2014 Proceedings 2014
DOI: 10.1109/icsens.2014.6985089
|View full text |Cite
|
Sign up to set email alerts
|

A low-power gas sensor for environmental monitoring using a capacitive micromachined ultrasonic transducer

Abstract: We present a low-power gas sensor design based on a capacitive micromachined ultrasonic transducer (CMUT), for use on self-powered wearable platforms. Earlier a CMUT-based sensor, with 70-mW power consumption operating at 50 MHz, achieved ppt-level detection limit for chemical warfare agents. In this work we present a sensor operating at 4.33 MHz and consuming 0.77 mW for environmental monitoring. The sensor comprises a polymer-functionalized CMUT resonator in the feedback loop of a Colpitts oscillator. We fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For initial testing we used a 4.52 MHz device (Q=180) coated with a thin layer of polyisobutylene (PIB) and demonstrated an average sensitivity of 270 Hz/ppm within the range of 10–20 ppm of toluene concentration and a resolution of 12 ppb (Fig. 22)[33]. We have also implemented 6-, 8-, and 15-channel prototype arrays with a standard deviation of 1% in the parallel resonant frequency (4.5 MHz) in a 7×9 mm 2 die area.…”
Section: Resultsmentioning
confidence: 99%
“…For initial testing we used a 4.52 MHz device (Q=180) coated with a thin layer of polyisobutylene (PIB) and demonstrated an average sensitivity of 270 Hz/ppm within the range of 10–20 ppm of toluene concentration and a resolution of 12 ppb (Fig. 22)[33]. We have also implemented 6-, 8-, and 15-channel prototype arrays with a standard deviation of 1% in the parallel resonant frequency (4.5 MHz) in a 7×9 mm 2 die area.…”
Section: Resultsmentioning
confidence: 99%
“…Seok et al have observed fully reversible ethanol detection for 50 min, exposing the device to nine different concentrations [ 133 ]. Other sensors have only been demonstrated for single minutes ranges [ 102 , 127 ]. Research on these aspects is relatively scarce and focus is typically applied to primary concerns, such as demonstration of working principles, and signal processing.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly understood that mass-loading of the resonant sensing structure, the resonant frequency will shift [ 94 , 95 , 96 , 97 ], and in most cases, developers tend to prove the linear relationship between the shift of the resonant frequency to the quantity of molecules of interest. This is understandable since SUGS operation can be maintained then by tracing the frequency of the free-running oscillator [ 102 ]. However, there can be several different interactions between the gas molecules and the functional layer.…”
Section: Functional Materialsmentioning
confidence: 99%
“…The cavities and bottom electrodes are formed on a borosilicate glass wafer [see Fig. 17(a) and (b)] [40]. The device layer of an SOI wafer bonded on glass forms the vibrating plate on top of vacuum-sealed cavities.…”
Section: E Capacitive Micromachined Ultrasonic Transducers For Volatmentioning
confidence: 99%